Les places traditionnelles de Porto-Novo (Bénin) comme communs : entre mise en valeur des espaces urbains et promotion des pratiques sociales et culturelles - Elizabeth Auclair; Élise Garcia (Développement Durable et Territoires)
The traditional places in Porto Novo are urban spaces which combine religious, cultural, social and economic functions. These places are neither entirely public nor private as they symbolically “belong” to the families, the communities who live there; they therefore can be considered as commons. They illustrate a complex combination between opposite dimensions such as material/immaterial, sacred/secular, public/private, visible/invisible. This article examines the perceptions and representations of the inhabitants, the dynamics induced by the rehabilitation of the traditional places and the involvement of local artists. Culture, memories, traditions, and religious practices are elements which contribute to the place and sense of belonging, and participate in defining these places as commons.